AI-Based Digital Marketing Strategy to Increase Consumer Loyalty in the Industry 5.0 Era - Wardana, Wikrama (Dinasti International Journal of Digital Business Management, 2025)
The development of technology in the industrial era 5.0 has encouraged companies to adopt digital marketing strategies based on artificial intelligence (AI) in building consumer loyalty. This study aims to analyze the effect of AI-based digital marketing strategies on consumer loyalty with consumer trust in personal data management as a moderator variable. The research method used is a quantitative approach with a purposive sampling technique on 310 active users of e-commerce platforms in Indonesia. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0. The results of the study indicate that AI-based digital marketing strategies have a positive and significant effect on consumer loyalty. In addition, consumer trust in personal data management has been shown to strengthen the relationship between AI-based strategies and consumer loyalty. This study emphasizes the importance of implementing ethical and consumer-focused technology in building long-term loyalty. The practical implication of this study is the need for companies to not only develop marketing technology innovations, but also build consumer trust through transparency and personal data protection.